Art museum - Wang, Zhi; JTart Publishing & Media ([Guangzhou, China] : JTart Publishing & Media, 2012)
The book collects the best architectural art and cultural projects, including museums, exhibition halls, libraries, theaters, art galleries, and cultural activity centers. These projects incorporate a strong design concept, layout, plans, faades, and traditional architectural inspirations with a number of carefully selected sketches, design drawings, renderings, technical drawings, sections, schedule drawings, detail drawings, and photographs. The book includes prominent cultural buildings from five continents, in a diverse selection of countries including the United Kingdom, France, Germany, Italy, Spain, the Netherlands, Belgium, Switzerland, Norway, Denmark, Poland, Croatia, United States, Canada, Colombia, Libya, Equatorial Guinea, Japan, Korea, China, and the United Arab Emirates. Beautiful illustrations accompany unique ideas, making this the perfect book for architecture and design novices and professionals.
Museum/Exhibition hall -- Cultural/Activity center -- Art building.
Series no. from book jacket.
Keywords: Museum architecture; Exhibition buildings; Public buildings; Architecture, Modern -- 20th century -- Designs and plans; Architecture, Modern -- 21st century -- Designs and plans